A Cap CumEye-like Obstacle Detector System havingGPS Facility For The Blind People - Kumar Singh, Rohit; Sharma, Dipak; Sen, Srirup; Bandyopadhyay, Dipan (International Journal of Computer Sciences and Engineering, 2025)
As the world gets more and more technologically advanced, we are in search of new technologieswhich will come to the help of physically challenged persons.Modern technologies have enriched us, eases our life a great deal but it is a high time to think of those people who are completely physically challenged. We shouldproperly utilizeourscience and technology so that all can enjoy equal benefits in the society.As a small step, we are trying to present a modern technology nourished system which hopefully reduces the difficulties of the blind people in their daily life to some extent. In this paper, we are presenting the design and implementation of a simple, low cost and flexible cap-likeObstacles Detector system which basically usesan Ultrasonic Sensor and GPS Module. ThisESP8266 Microcontroller based system which is designed for visually impaired persons can be upgraded in the future in better sophisticated form integrating a navigate system,camera or incorporating voice recognition like facilities. We believe small steps fromall of us can change their life in a big way.